Avoiding the misuse of social media by employees. Issue 5 (May 2016) - Taylor, Mark; Haggerty, John; Gresty, David; Wren, Chris; Berry, Tom
Abstract : Social networking applications such as Facebook, Twitter and YouTube are increasingly being used in various ways by organisations. Organisations may adopt the use of social media for a variety of reasons including engaging with customers and clients, and supporting communication between employees. 1–3 Although social media can potentially support communication between employees, care needs to be taken that they are used in a manner appropriate for relevant business purposes, at all times. Social networking applications are increasingly being used by organisations to engage with customers and support communications between employees. However, care needs to be taken that social media are used in a manner appropriate to relevant business purposes. This articles examines the potential misuse of social media by employees, the UK legislation relevant to such misuse, and also explores approaches by which organisations can attempt to limit such misuse.